A tunable human intestinal organoid system achieves controlled balance between self-renewal and differentiation - Li Yang; Xulei Wang; Xingyu Zhou; Hongyu Chen; Sentao Song; Liling Deng; Yao Yao; Xiaolei Yin (Nature Communications)
Abstract A balance between stem cell self-renewal and differentiation is required to maintain concurrent proliferation and cellular diversification in organoids; however, this has proven difficult in homogeneous cultures devoid of in vivo spatial niche gradients for adult stem cell-derived organoids. In this study, we leverage a combination of small molecule pathway modulators to enhance the stemness of organoid stem cells, thereby amplifying their differentiation potential and subsequently increasing cellular diversity within human intestinal organoids without the need for artificial spatial or temporal signaling gradients. Moreover, we demonstrate that this balance between self-renewal and differentiation can be effectively and reversibly shifted from secretory cell differentiation to the enterocyte lineage with enhanced proliferation using BET inhibitors, or unidirectional differentiation towards specific intestinal cell types by manipulating in vivo niche signals such as Wnt, Notch, and BMP. As a result, we establish an optimized human small intestinal organoid (hSIO) system characterized by high proliferative capacity and increased cell diversity under a single culture condition. This optimization facilitates the scalability and utility of the organoid system in high-throughput applications.